(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
The research aimed to study the physical characteristics of the bottom sediments, a part of a course of Euphrates River in AL-Nasiriyah city, with a length of 7.5 km. Ten cross-sections were identified that were used as stations for sampling the bottom sediments. One cross-section was divided into three sections, including (the two banks and the middle of the river). Three samples were mixed for each section to obtain one homogeneous sample for each cross-section. After analyzing these samples in the laboratory, it was concluded:There is a difference in the granular size of the bottom sediments according to the locations of cross-sections, as they are affected by each of the facilities built on the river, such as bridges. The values of d50* ranged between (0.088 - 0.15 mm), while the values of d90* ranged between (0.3 - 0.67 mm). The results also indicated that the bottom sediments in the course of the Euphrates River have a sandy gradient, as the percentage of sand ranges between (53.1- 68.6%), and the percentage of silt was (14.3 - 31.7%), while the percentage of clay ranged between (11.3 -19.8%), at the level of all samples of the studied cross-sections.